Craniopharyngioma in Adults - Zoicas, Flavius; Schöfl, Christof (Frontiers in Endocrinology, 2012)
Craniopharyngiomas are slow growing benign tumors of the sellar and parasellar region with an overall incidence rate of approximately 1.3 per million. During adulthood there is a peak incidence between 40 and 44 years. There are two histopathological types, the adamantinomatous and the papillary type. The later type occurs almost exclusively in adult patients. The presenting symptoms develop over years and display a wide spectrum comprising visual, endocrine, hypothalamic, neurological and neuropsychological manifestations. Currently, the main treatment option consists in surgical excision followed by radiation therapy in case of residual tumor. Whether gross total or partial resection should be preferred has to be balanced on an individual basis considering the extent of the tumor (e.g. hypothalamic invasion). Although the overall long-term survival is good it is often associated with substantial morbidity. Preexisting disorders are often permanent or even exacerbated by treatment. Endocrine disturbances need careful replacement and metabolic sequelae should be effectively treated. Regular follow-up by a multidisciplinary team is a prerequisite for optimal outcome of these patients.